Hubungan Pengetahuan Dan Sikap Ibu Post Partum Terhadap Perawatan Tali Pusat Terbuka Di Wilayah Kerja Puskesmas Tebing - Jati Luya Panggabean; Rachmawaty M. Noer; Yulianti Wulandari (Inovasi Kesehatan Global, 2024)
Neonatal tetanus and umbilical cord infections are persistent causes of morbidity and mortality in various countries. Every year 500,000 babies die from neonatal tetanus, and 460,000 babies die from bacterial infections. This research is quantitative using a cross sectional approach. The research population was postpartum mothers in the Tebing Health Center working area in February 2023. Sampling using purposive sampling obtained 38 respondents as samples. The results showed that 16 respondents (42.1%) who had good knowledge carried out open umbilical cord care in the good category, then 18 respondents who had a positive/supportive attitude (47.3%) also carried out open umbilical cord care well. category. In conclusion, there is a significant relationship between knowledge and open umbilical cord care with a p-value of 0.001 α 0.05 and there is a significant relationship between maternal attitudes and open umbilical cord care with a p-value of 0.000 - 0.05. It is hoped that health workers will provide education by practicing open umbilical cord care techniques to increase the knowledge and attitudes of postpartum mothers in caring for the umbilical cord.